Phosphorus Acquisition and Utilization in Plants - Lambers, Hans (Annual review of plant biology, 2022)
Tremendous progress has been made on molecular aspects of plant phosphorus (P) nutrition, often without heeding information provided by soil scientists, ecophysiologists, and crop physiologists. This review suggests ways to integrate information from different disciplines. When soil P availability is very low, P-mobilizing strategies are more effective than mycorrhizal strategies. Soil parameters largely determine how much P roots can acquire from P-impoverished soil, and kinetic properties of P transporters are less important. Changes in the expression of P transporters avoid P toxicity. Plants vary widely in photosynthetic P-use efficiency, photosynthesis per unit leaf P. The challenge is to discover what the trade-offs are of different patterns of investment in P fractions. Less investment may save P, but are costs incurred? Are these costs acceptable for crops? These questions can be resolved only by the concerted action of scientists working at both molecular and physiological levels, rather than pursuing these problems independently.